Glossary of Energy - Swedish Language Council, Institute for Language and Folklore (Institute for Language and Folklore, 2023)
Multilingual glossary containing terms related to energy, it was originally developed at TNC in cooperation with Energiforskningsnämden. The Council for Technical Terminology, RTT provided the Norwegian terms and most of the terms in other languages have been provided by EEC:s translation agency in Luxembourg.

The glossary contains 638 terms in Swedish. The terms are also translated to German, Norwegian, Danish, French and English.

Flerspråkig terminologisamling som rör energitermer. Ordlistan har utarbetats av TNC i samarbete med Energiforskningsnämnden. Rådet for teknisk terminologi, RTT har lämnat dom norska termerna och av de övriga språkens motsvarigheter har dom flesta lämnats av EGs (Europeiska gemenskapen) översättningsbyrå i Luxemburg.

Ordlistan har varit på remiss i 120-tal instanser.

Samlingen innehåller 638 termer på svenska. Termerna är även översatta till tyska, norska, danska, franska, och engelska.
Energiordlista
Keywords: Terminology; Terminologi; Energy; Energi; Glossaries; Ordlistor; Swedish Centre for Technical Terminology; Tekniska nomenklaturcentralen; Multilingualism; Flerspråkighet; Languages and Literature; Språk och litteratur